Fasciolosis epidemiology and prospects for its control at Cape Verde Islands - Rosa, Fernanda (2004)
Lymnaea species and their infection by Fasciola gigantica were investigated at Santiago, St. Antão, S. Nicolau, Sal and Fogo Islands. The study of the fluctuations of Lymnaea natalensis populations and the prevalence of F. gigantica in the snail was performed between October/November 1994 and March/April 1999. At Santiago Island, Lymnaea natalensis was found in 20 habitats and F. gigantica infected snails were detected in 14. Uninfected L. auricularia were identified in 6 habitats at Sto. Antão. On 4097 freshwater snails studied, 1383 (33,76%) were collected on October/November and 2714 (64,24%) on March/April. The snail density and the prevalence of Fasciola gigantica infection were irregular and tended to be higher during March/April in almost all of the habitats. The prevalence of Fasciola gigantica in cattle was 39,17% out of 120 cattle slaughtered at Praia abattoir. F. gigantica eggs output were registered on faeces from cattle (17,82%) and donkeys (14,29%) collected at the snails habitats. The association of the intra-mollusc and cattle infections was difficult to establish. However, a decrease on the prevalence of intra-mollusc infection was observed, followed by a reduction on the cattle infection in the following year. This pattern seems to be more evident after the 1995 heavy rain period. The animals at risk, as well as the freshwater snail and Fasciola habitats, related to the increasing diagnosis of fascioliasis in man, show that this disease is still a serious problem in animal production and in human health. Nevertheless, the improvement of irrigation systems by reducing available water at the habitats for the snail/trematode development, seems to be an effective control measure for their decrease.